Modifikasi Altmant Z Score dan Integrasi Nilai Islam sebagai Factor Pengaruh Financial Distress terhadap RGEC (Studi Kasus BNI Syariah, BRI Syariah, Bank Syariah Mandiri) - Sahrani Sahrani; Mutmainah juniawati (Universitas Muhammadiyah Prof Dr Hamka, 2020)
The survival of a company/ institution depends on several things. When a company / institution starts showing poor health, a financial manager must immediately take action so that the company / institution approaches safe conditions, one of the methods used is through financial distress identification. Identification of financial distress conditions is more important than bankruptcy, because companies / institutions will definitely experience financial distress first and then go bankrupt. Islamization of Knowledge is not a new thing in the development of Islamic economics. The integration of Islamic values